Bisimulation for reactive frames - Figueiredo, Daniel (2018)
Reactive frames are those whose structure is not fi xed but can vary according to the path chosen. This kind of frame has been study and both a logic and an axiomatization for it were already developed. In this paper we take this study further and de fine a notion of bisimulation for reactive models. We show that the logic introduced by Marcelino for these frames is invariant under our notion of bisimulation. Finally, we proof the Hennessy-Milner theorem for a class of reactive models.